Information fusion and geographic information systems (IF AND GIS 2013) : Environmental and Urban challenges - Claramunt, Christophe; Schrenk, Manfred; Korolenko, Kyrill; Popovich, Vasily (Lecture Notes in Geoinformation and Cartography, 2014)
The Workshop Proceedings reflect problems of advanced geo-information science with a special emphasis on environmental and urban challenges. The Proceedings incorporate papers presented by leading scientists doing research on environmental issues from modeling to analysis, information processing and visualization. As well as practitioners engaged in GIS and GIS applications development. The Proceedings pay close attention to the problems of scientific and technological innovations as well application opportunities such as getting environmental and global warming problems under control, as well as the monitoring, planning and simulation of urban systems with respect to economic trends as related to: Artificial intelligence; GIS ontologies; GIS data integration and modeling; Environmental management ; Urban GIS; Transportation GIS; GIS data fusion; GIS and corporate information systems; GIS and real-time monitoring systems; GIS algorithms and computational issues; Landscape studies; Global warming; GIS and the Arctic sea; Novel and emerging GIS research areas; Maritime and environmental GIS; and Coastal GIS.